Atlas of Portuguese Emigration [English translation of Atlas da Emigração Portuguesa] - Pires, R. P.; Vidigal, I.; Pereira, Cláudia; Azevedo, J.; Moura-Veiga, C. (2025)
Emigration in Portugal is a long-term and widespread phenomenon that has seen a new boom in the 21st century. Between 2001 and 2020, an average of more than 75,000 people will have left Portugal every year. In addition to the previous large migratory waves in the second half of the 20th century, the most recent departures have contributed to the creation of a large emigrant population. Today, more than 2.1 million Portuguese emigrants live around the world. Measured in relative terms, Portuguese emigration is the largest in Europe and the eighth largest in the world. This Atlas, produced by the permanent team of researchers at the Emigration Observatory and published by Mundos Sociais, compiles and analyses the statistical information available on the current state of Portuguese emigration.